The religious phenomenon in Sociološki pregled/ Sociological review - Andjelkovic, Petar Miroslav (Sociološki pregled, 2018)
Sociološki pregled/ Sociological Review, “the frst true Yugoslav sociological journal” (Milovan Mitrović), was launched, as emphasized in the introduction of the frst issue “to contribute [...] to the progress of social sciences in our country”, therefore, starting with world and domestic experiences “to take a step further in the study of social life”. Tis journal has honorably and successfully carried out its mission and has been a place to present advanced ideas and views (to the extent that the time allowed). Tis was the place where ideas for founding special sociological sciences were presented for the frst time, such as the sociology of religion. Having in mind the importance of religion for people and society, understanding the religious phenomenon has had a special signifcance at all times. The subject of this paper is the analysis of all papers published in Sociološki pregled/ Sociological Review, from the frst issue to date, that considered and interpreted the religious phenomenon from diﬀerent aspects. Using the method of content analysis and discursive analysis of all texts that appeared in the observed period, the aim of the paper is to determine, on the basis of the presented standpoints, the main features of the discourse on the religious phenomenon presented in Sociološki pregled/ Sociological Review. In the article, the author strives to provide a sociological insight into the development of sociology of religion in the Yugoslav area, and its particular eﬀorts to reach and to comprehend all the complexity of the religious phenomenon.